Exploring the virulence gene interactome with CRISPR/dCas9 in the human malaria parasite - Bryant, Jessica M; Baumgarten, Sebastian; Dingli, Florent; Loew, Damarys; Sinha, Ameya; Claës, Aurélie; Preiser, Peter R; Dedon, Peter C; Scherf, Artur (Molecular systems biology, 2020)
Mutually exclusive expression of the var multigene family is key to immune evasion and pathogenesis in Plasmodium falciparum , but few factors have been shown to play a direct role. We adapted a CRISPR‐based proteomics approach to identify novel factors associated with var genes in their natural chromatin context. Catalytically inactive Cas9 (“dCas9”) was targeted to var gene regulatory elements, immunoprecipitated, and analyzed with mass spectrometry. Known and novel factors were enriched including structural proteins, DNA helicases, and chromatin remodelers. Functional characterization of Pf ISWI, an evolutionarily divergent putative chromatin remodeler enriched at the var gene promoter, revealed a role in transcriptional activation. Proteomics of Pf ISWI identified several proteins enriched at the var gene promoter such as acetyl‐CoA synthetase, a putative MORC protein, and an ApiAP2 transcription factor. These findings validate the CRISPR/dCas9 proteomics method and define a new var gene‐associated chromatin complex. This study establishes a tool for targeted chromatin purification of unaltered genomic loci and identifies novel chromatin‐associated factors potentially involved in transcriptional control and/or chromatin organization of virulence genes in the human malaria parasite. Synopsis CRISPR/dCas9‐based proteomics is used to purify specific DNA regulatory elements in their natural chromatin context and to identify novel chromatin factors associated with virulence genes in the human malaria parasite, Plasmodium falciparum . dCas9 immunoprecipitation and mass spectrometry identify proteins previously implicated in var gene biology in addition to novel factors, including a putative chromatin remodeler, ISWI. Proteomic analysis of ISWI reveals a new var gene‐associated complex comprising a putative MORC family protein and an ApiAP2 transcription factor. ISWI binds to promoter regions and plays a role in transcriptional activation of genes, including the active var gene in ring stage parasites. Graphical Abstract CRISPR/dCas9‐based proteomics is used to purify specific DNA regulatory elements in their natural chromatin context and to identify novel chromatin factors associated with virulence genes in the human malaria parasite, Plasmodium falciparum .